Arianespace catalogue 5 - Arianespace (France : Arianespace, 1998)
Arianespace, through its constant contact with spacecraft operators throughout the world, has repeteadly demonstrated its ability to anticipate the market's needs and to adapt its offer to provide greater customer value. Beyond the last qualification flight on October 21st, 1998 with Ariane 503, Arianespace is already preparing for a future which demands still more performance, more versatility, more operational flexibility and more launch capacity
System requirements: Power Macintosh, System 7.5 or more recent version, 16 Mb of RAM (24Mb or more recommended), 256 colour display (24 bits recommended), CD-ROM drive (4x); PC: entium 133 (Pentium 166MMX recommended), Windows 3.11, 95, 98 or NT 4.0, 16 Mb of RAM (24 Mb or more recommended); QuickTime driver
Keywords: Aircraft industry; Aerospace industries